How to know a person : the art of seeing others deeply and being deeply seen - Brooks, David, 1961- (Random House, 2023)
Drawing from the fields of psychology and neuroscience and from the worlds of theater, philosophy, history and education, one of the nation's leading writers and commentators helps us become more understanding and considerate toward others, and to find the joy that comes from being seen.